Dietary whey supplementation in experimental models of wound healing - YALÇIN, AHMET SUHA; VELİOĞLU ÖĞÜNÇ, AYLİZ (VERLAG HANS HUBER, 2008)
Whey is a dairy product containing milk serum proteins with diverse biological effects. In this study, the effect of dietary whey supplementation on wound healing was investigated. Rats were fed a standard or whey-supplemented diet for three weeks. Wound healing parameters, glutathione, and lipid peroxide levels were determined three days after the application of two different models of wound healing, i.e. laparotomy and colonic anastomosis. Dietary whey supplementation significantly increased glutathione levels and suppressed lipid peroxidation after experimental laparotomy and colonic anastomosis. Bursting pressures, hydroxyproline, and cytokine levels were not changed. Our results show that dietary whey supplementation increases glutathione synthesis and cellular antioxidant defense. Long-term effects of whey feeding on wound healing remains to be investigated.
Keywords: anastomosis; glutathione; lipid peroxidation; whey; wound healing; GLUTATHIONE; PROTEINS; PROMOTES